The influence of climate change in Superpave binder selection for Chile. Issue 3 (2nd April 2020) - Delgadillo, Rodrigo; Arteaga, Leandro; Wahr, Carlos; Alcafuz, Ricardo
Abstract : One of the relevant effects of anthropogenic climate change has been an anomalous increase in temperature near the earth's surface. In the context of pavement engineering, materials that are thermally susceptible could be affected by these changes. For this reason, the possible effects of global warming in binder selection for asphalt pavements in Chile were studied. Two global warming scenario results obtained with MICRO5 model plus local downscaling with WRF model were used. The estimated temperature changes were calculated for the period 2030–2059 for the 94 weather stations previously used for the Chilean Superpave zonings. Three pavement temperatures models were used together with these new air temperature databases: SHRP, LTPP 2.1 and LTPP 3.1. The results were compared with the original Superpave zonings obtained with the same models. A significant number of stations underwent a change in PG grade for the period considered. Most of the predicted changes were increased in the high-temperature PG grade. The areas of use for the softer binder PG52-34 gradually decreased, while the areas for the stiffer PG64-22 increased. A new even stiffer binder PG70-16 had to be introduced into the new Superpave zonings.